Jordanian Journalists' Attitudes Toward Persons With Disability within the Social Model (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
. The goal of this study is to identify Attitudes of Jordanian journalists towards persons with disabilities within social model concepts, and the relationship of these Attitudes with the level of media practice on disability subjects, demographic and media factors of the study through polling journalists’ attitudes towards the disabled The survey methodology was used in the study which targets journalists and media people, who are members of the Jordan Press Association. The number of the respondents was( 212), as the researcher relied on a questionnaire for there search. The study results showed that Jordanian journalists hold positive attitudes towards people with disabilities and it showed differences attributed to the variables of the study, except for variables of marital status and experience on the Attitudes scale. The results also showed that print media and civil service employees have higher averages than the audio-visual media and media outlets owned by the private sector, and also revealed a contradiction between media practice and the overall attitude scale. In light of the results, the study recommends that workshops be organized for journalists and media personnel to acquaint them with the rights of persons with disabilities and to prepare a directory that contains positive titles that should be used and negative titles that should be avoided. The study also calls for focusing on the integration of persons with disabilities into society to change societal negative attitude towards them.